DEVELOPING AND EVALUATING ISLAMIC-BASED ELT MATERIALS: A SYSTEMATIC REVIEW OF DESIGN PRINCIPLES, VALIDITY, AND CLASSROOM IMPACT - Efriswan Situmorang (Universitas Negeri Islam Sumatera Utara, 2025)
This systematic literature review synthesizes empirical research on Islamic-based English Language Teaching (ELT) materials to clarify (1) how such materials are designed, (2) how their validity and feasibility are evaluated, and (3) what classroom impacts are reported. Using a structured SLR procedure, the study searched Scopus for open-access, English-language journal articles (2015-2025) within social sciences and applied explicit inclusion/exclusion criteria through staged screening, yielding seven eligible studies. Data were extracted with a predefined framework and analyzed through qualitative descriptive synthesis and thematic analysis aligned to the review questions. Findings show that Islamic value integration is most often implemented through systematic development models (e.g., ADDIE/4D and related R&D procedures) and operationalized via contextualized values such as religious moderation, local wisdom (e.g., Acehnese/Minangkabau), project-based ethics (FAST), and multimodal digital resources. Evidence of validity and feasibility largely relies on expert judgment, teacher/student practicality feedback, and limited trials, with relatively few studies reporting transparent revision cycles or robust re-testing. Reported impacts most consistently include greater relevance, engagement, and perceived meaningfulness, while measurable language gains are documented less frequently, and long-term character outcomes remain under-instrumented. The review implies a need for more longitudinal/quasi-experimental evaluations, clearer value operationalization, and multidimensional outcome measures to enhance transferability across Islamic educational contexts.